(untitled) (Research, Society and Development, 2024)
Objective: To analyze the possible interference of the use of screens in the quality of sleep of children. Methods: This is a systematic literature review. Searches for scientific articles were carried out on the websites PubMed, SciELO and Lilacs, using the descriptors “electronic devices”, “children”, “infant”, “sleep”, “child development” and “screen time”, available on Descriptors in Health Sciences (DeCS), combined by the Boolean operators “AND” and “OR”. From the search, 944 articles were found, among which 11 were part of the final sample after applying PRISMA. Results: Excessive use of screens , defined as screen time (TT) greater than 2 hours/day, promotes a maladaptation in the establishment of the sleep-wake cycle, increasing the release of hormones that cause delay and poor quality of sleep. Of the 11 articles selected, 6 related poor sleep, difficulty falling asleep and nighttime awakenings when using screens. In addition to these, obesity, sedentary lifestyle, inattention, postural instability and affective problems are also correlated with screens. Conclusion: From the analysis of the aforementioned studies, it was possible to infer that The use of digital devices among children is a risk factor for changes in the quality and quantity of sleep and in other areas of child development.